The Impact of Financial Ratios on Corporate Performance in Southeast Asia: A Comparison of Pre- and Post-COVID-19 Pandemic - Badar, Dadan Samsul; Nurgraha, Nugraha; Supriyatna, Yayat; Purnamasari, Imas (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the impact of financial ratios on corporate performance in Southeast Asia before and after the COVID-19 pandemic. This research uses secondary data obtained from the annual financial statements of companies listed in Indonesia, Malaysia, and Singapore during the 2019–2023 period. The method used is panel data regression with a Random Effect model, which was selected based on the results of the Hausman and Lagrange Multiplier tests. The results indicate that the Debt Ratio (DR) and firm size have a significant negative impact on financial performance, measured by Return on Assets (ROA). Meanwhile, the Current Ratio (CR) does not show a significant effect on ROA. Additionally, the findings also suggest that the COVID-19 pandemic negatively impacted corporate performance during the period, but there was no significant difference in performance post-pandemic. This research provides valuable insights for corporate managers and policymakers to formulate more effective financial strategies in the face of global crises. Keywords: Financial Ratios, Corporate Performance, COVID-19 Pandemic, Panel Data Regression, Southeast Asia